2015
DOI: 10.1016/j.tips.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Arginase: an old enzyme with new tricks

Abstract: Arginase has roots in early life forms. It converts L-arginine to urea and ornithine. The former provides protection against NH3; the later serves to stimulate cell growth and other physiological functions. Excessive arginase activity in mammals has been associated with cardiovascular and nervous system dysfunction and diseases. Two relevant aspects of this elevated activity may be involved in these disease states. First, excessive arginase activity reduces the supply of L-arginine needed by nitric oxide (NO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
214
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 262 publications
(235 citation statements)
references
References 129 publications
6
214
0
8
Order By: Relevance
“…Because NO serves to relax the smooth muscles of the corpus cavernosum, inhibition of ARG, at this time, is useful for increasing the supply of the substrate to the action of eNOS [93].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because NO serves to relax the smooth muscles of the corpus cavernosum, inhibition of ARG, at this time, is useful for increasing the supply of the substrate to the action of eNOS [93].…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that ARG activity is related to tumour progression, since the formation of polyamines and proline that are the result of enzyme action can contribute to cell proliferation and tumour growth, as shown by studies that have found a relationship of risk between the increased expression of ARG 2 and the appearance of disease [93,105]. Thus, ARG inhibition has the potential to curb this process, which might work in favour of the action of other anticancer substances.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations